2018
DOI: 10.1101/259754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Audible Feedback Improves Internal Model Strength and Performance of Myoelectric Prosthesis Control

Abstract: Myoelectric prosthetic devices are commonly used to help upper limb amputees perform activities of daily living, however amputees still lack the sensory feedback required to facilitate reliable and precise control. Augmented feedback may play an important role in affecting both short-term performance, through real-time regulation, and long-term performance, through the development of stronger internal models. In this work, we investigate the potential tradeoff between controllers that enable better short-term … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…We anticipate that real use of these methods may utilise the economic feedback protocol hypothesized by Dosen et al to gradually reduce overall reliance on feedback whilst also providing intermittent information to ensure internal models remain stable [64]. It may be the case that other forms of feedback, such as artificial proprioception [23], vibro-tactile stimulation [65], or audio augmented feedback [66] will be more appropriate to provide information about the current state, in order to facilitate the development of the internal model.…”
Section: Effect Of Feedback On Performancementioning
confidence: 99%
“…We anticipate that real use of these methods may utilise the economic feedback protocol hypothesized by Dosen et al to gradually reduce overall reliance on feedback whilst also providing intermittent information to ensure internal models remain stable [64]. It may be the case that other forms of feedback, such as artificial proprioception [23], vibro-tactile stimulation [65], or audio augmented feedback [66] will be more appropriate to provide information about the current state, in order to facilitate the development of the internal model.…”
Section: Effect Of Feedback On Performancementioning
confidence: 99%
“…Sensory feedback remains a research priority for prosthesis users 6 . Several feedback methods have been proposed over the past decades, including vibrotactile [7][8][9][10][11] , electrotactile 8 , skin stretch 7 , audio [12][13][14] and visual 15 modalities 16,17 . More complex feedback modalities like peripheral nerve stimulation 18 and vibration-induced illusory kinesthesia 19 have also been introduced to great effect.…”
Section: Introductionmentioning
confidence: 99%
“…More complex feedback modalities like peripheral nerve stimulation 18 and vibration-induced illusory kinesthesia 19 have also been introduced to great effect. Sensory feedback typically falls into two categories: tactile feedback of grasping force 9,11,18 , and proprioceptive feedback of limb movement 7,8,10,[12][13][14][15]19 . Vision is capable of estimating grasping force similarly to tactile feedback 20 , though several grasping force feedback studies have still shown significant benefit to prosthesis control with vision present.…”
Section: Introductionmentioning
confidence: 99%